Probabilistic Sensitivity Analysis to Understand the Influence of Micromechanical Properties of Wood on Its Macroscopic Response - Saavedra-Flores, E; Guzman-Inostroza, C (Elsevier Ltd, 2017)
This paper investigates the influence of the uncertainty in different micromechanical properties on the variability of the macroscopic response of cross-laminated timber plates, by means of a probabilistic sensitivity analysis. Cross-laminated timber plates can be modelled using a multiscale finite element approach which although suitable, suffers from high computational cost. Investigating parametric importance can incur considerable time penalty since conventional sensitivity analysis relies on a large number of code evaluations to produce accurate results. In order to address this issue, we build a statistical approximation to the code output and use it to perform sensitivity analysis. We investigate the effect of a collection of parameters on the density and Young s moduli of wood. Additionally, the influence on the response of cross-laminated timber plates subject to bending, in-plane shear and compression loads is investigated due to its relevance within the engineering community. The presented results provide a practical insight into the importance of each micromechanical parameter, which allows research effort to be focused on important wood properties. © 2017 The Authors